"Triple negative breast cancer": Translational research and the (re)assembling of diseases in post-genomic medicine. (October 2016) - Keating, Peter; Cambrosio, Alberto; Nelson, Nicole C.
Abstract: The paper examines the debate about the nature and status of "Triple-negative breast cancer", a controversial biomedical entity whose existence illustrates a number of features of post-genomic translational research. The emergence of TNBC is intimately linked to the rise of molecular oncology, and, more generally, to the changing configuration of the life sciences at the turn of the new century. An unprecedented degree of integration of biological and clinical practices has led to the proliferation of bio-clinical entities emerging from translational research. These translations take place between platforms rather than between clinical and laboratory settings. The complexity and heterogeneity of TNBC, its epistemic and technical, biological and clinical dualities, result from its multiple instantiations via different platforms, and from the uneven distribution of biological materials, techniques, and objects across clinical research settings. The fact that TNBC comes in multiple forms, some of which seem to be incompatible or, at least, only partially overlapping, appears to be less a threat to the whole endeavor, than an aspect of an ongoing translational research project. Discussions of translational research that rest on a distinction between basic research and its applications fail to capture the dynamics of this new domain of activity, insofar as application is built-in from the very beginning in the bio-clinical entities that emerge from the translational research domain. Highlights: Targeted clinical interventions simultaneously explore the molecular mechanisms of normal and pathological processes. Understanding innovation in the life sciences requires examining the content and temporal order of bio-clinical practices. Translational research takes place between platforms rather than between clinical and laboratory settings. The distinction between basic research and its applications fails to capture the dynamics of translational research. Competing definitions of Triple-Negative Breast Cancer reflect the need to define the platform used for (re)producing it.